CRISPR/Cas9: A Practical Approach in Date Palm Genome Editing - Sattar, Muhammad N.; Iqbal, Zafar; Tahir, Muhammad N.; Shahid, Muhammad S.; Khurshid, Muhammad; Al-Khateeb, Abdullatif A.; Al-Khateeb, Suliman A. (Frontiers in Plant Science, 2017)
The genetic modifications through breeding of crop plants have long been used to improve the yield and quality. However, precise genome editing (GE) could be a very useful supplementary tool for improvement of crop plants by targeted genome modifications.. Various GE techniques including ZFNs, TALENs and most recently CRISPR/Cas9 based approaches have been successfully employed for various crop plants including fruit trees. CRISPR/Cas9 based approaches hold great potential in GE due to their simplicity, competency and versatility over other GE techniques. However, to the best of our knowledge no such genetic improvement has ever been developed in date palm - an important fruit crop in Oasis agriculture. The applications of CRISPR/Cas9 can be a challenging task in date palm GE due to its large and complex genome, high rate of heterozygosity and outcrossing, in vitro regeneration and screening of mutants, high frequency of SNPs in the genome and ultimately genetic instability. In this review, we addressed the potential application of CRISPR/Cas9-based approaches in date palm GE to improve the sustainable date palm production. The availability of the date palm whole genome sequence has made it feasible to use CRISPR/Cas9 GE approach for genetic improvement in this species. Moreover, the future prospects of GE application in date palm are also addressed in this review.